CHEMICAL AND PHYSICAL ANALYSIS OF SANDSTONE ROCK FROM BOTUCATU FORMATION - João Carlos Correa; Francisco Assis Cavallaro; Rafael H. L. Garcia; Rodrigo Sousa Santos; Rafael Aquino Amade; Thiago Lynyker da Silva Bernardes; Alexandre França Velo; Carlos Henrique Mesquita; Margarida Mizue Hamada (Brazilian Journal of Radiation Sciences, 2021)
The productive capacity of the Guarani Aquifer System is subject to variations along its length, due to its complex structural and compositional heterogeneity. Several parameters may influence the quality of this reservoir rock, such as its mineralogical and textural constitution, as well as the physicochemical processes, since its diagenesis is not the same throughout the aquifer, influencing the water productivity in wells in different locations. Such parameters are useful in the geoscience studies for the elaboration of diagenetic models for the prediction of the reservoir quality. In this work, several properties of the sandstone rock from Botucatu Formation were determined using different techniques, such as geotechnical tests, optical microscopy (MO), electron scanning microscopy (SEM), X-ray Fluorescence and X-ray diffraction. The results indicate that the studied sandstones have characteristics of the reservoir rocks, with potential for water storage.